Role of internal variability of climate system in increase of air temperature in Wrocław (Poland) in the years 1951–2018 - Marsz, Andrzej A.; Styszyńska, Anna; Bryś, Krystyna; Bryś, Tadeusz (Quaestiones Geographicae, 2021)
In the course of analysing the annual air temperature in Wrocław (TWr), a rapid change of the thermal regime was found between 1987 and 1989. TWr increased by >1°C, a strong, statistically significant positive trend emerged. The analysis of processes showed that strong warming in the cold season of the year (December–March) occurred as a result of an increase in the NAO intensity and warming in the warm season because of increased sunshine duration in Wrocław (ShWr). Multiple regression analysis has shown that the winter NAO Hurrell’s index explains 15% of TWr variance, and the ShWr of the long-day (April–August) period 49%, whereas radiative forcing 5.9%. This indicates that the factors incidental to the internal variability of the climate system explain 64% of the TWr variability and the effect of increased CO2 concentration only ~6%. The reason for this rapid change of the thermal regime was a radical change in macro-circulation conditions in the Atlantic-European circular sector, which took place between 1988 and 1989. The heat, which is the cause of warming in Wrocław, comes from an increase in solar energy inflow (April–August) and also is transported to Europe from the North Atlantic surface by atmospheric circulation (NAO). These results indicate that the role of CO2 in shaping the contemporary temperature increase is overestimated, whereas the internal variability of the climate system is underestimated.